Possible Differences In The Mode Of Action Of Ditazole And Non-Steroidal Anti-Inflammatory Drugs As Potential Antithrombotic Agents - Sim, A K; McCraw, A P; Caprino, L; Antonetti, F; Morelli, L (Thrombosis and Haemostasis, 1981)
Ditazole (4,5-diphenyl-2-diethanolamino-oxazole), a weak anti-inflammatory drug, has been shown to be a potent inhibitor of platelet aggregation, adhesiveness and bleeding time. Acetylsalicylic acid (ASA), dipyridamole and a combination of these two drugs induced a platelet shape change which was much shorter lasting than their effect on platelet aggregation. Conversely, similar doses of ditazole induced a potent shape change but no effect on aggregation. Ditazole has now been shown to reversibly antagonise thromboxane A2 (TXA2)-induced contraction of rabbit aortic strips at an optimal concentration of 25 μm in the perfusate. Separately, over a dose range of 50-400 mg/kg/p.o., TXA2 production was inhibited between 39% and 85% in spontaneously clotted rabbit blood. In addition, we have shown that TXA2 formation following arachidonic acid-induced aggregation of platelet-rich plasma (PRP) is similarly inhibited. Ditazole however did not inhibit prostacyclin (PGI2) production in rabbit aortic rings following oral drug administration over a dose range of 50-400 mg/kg. At 1000 and 2000 mg/kg PGI2 production was inhibited by 23% and 41% respectively. TXA2 and PGI2 levels were measured by radioimmunoassay of their stable derivatives TXB2 and 6-keto-PGF1α. It is suggested that the mode of action of ditazole may be more specific than the cyclo-oxygenase/PG-synthetase blocking activity of most other non-steroidal anti-inflammatory drugs.